BULLYING BEHAVIOR TOWARDS STUDENTS IN ISLAMIC EDUCATIONAL INSTITUTIONS: IMPLEMENTATION OF PROBLEM SOLUTIONS - Hasanuddin, Hasanuddin; Tamuri, Ab. Halim; Chandra, Andy; Parinduri, Muhammad Abrar (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to find out how to implement problem solutions to bullying behavior that tends to occur in Islamic educational institutions. Islamic educational institutions, which in their curriculum are ensured to have a lot of character education content, are considered not optimal in giving strict sanctions to students who are perpetrators of bullying and all other dishonorable acts. This research uses a qualitative descriptive approach. To obtain research data, researchers used open interview techniques with informants. The participants in this study were students from 4 Integrated Islamic Middle Schools in Medan City, totaling 4 students. Data triangulation techniques were also used in this study by checking records from interviews, field notes, surveys and also documentation records from various data obtained. The results of the study show that bullying that occurs in several Integrated Islamic schools does not receive serious attention, teachers and schools often ignore this behavior by not providing consequences or punishments so that bullies feel rewarded or empowered for their actions. The school should not tolerate the slightest bit of disgraceful actions committed by students so that it becomes a deterrent effect for other students and parents are also required to be responsible for providing good ethical education in the family. teachers and schools often ignore this behavior by not giving consequences or punishments so that bullies feel rewarded or empowered for their actions. The school should not tolerate the slightest bit of disgraceful actions committed by students so that it becomes a deterrent effect for other students and parents are also required to be responsible for providing good ethical education in the family. teachers and schools often ignore this behavior by not giving consequences or punishments so that bullies feel rewarded or empowered for their actions. The school should not tolerate the slightest bit of disgraceful actions committed by students so that it becomes a deterrent effect for other students and parents are also required to be responsible for providing good ethical education in the family.